Ingles Performance and physiological response of juvenile tambaqui (Colossoma Macropomum, Curvier 1818) feeding with pequi oil (Caryocar Brasiliense, Camb) - Alysson Soares da Rocha; Rodrigo Diana Navarro (Acta Scientiarum. Animal Sciences, 2023)
The aim of the study was to evaluate the performance and physiological responses of juvenile tambaqui (Colossoma macropomum) fed diets containing pequi oil (Caryocar brasiliense, Camb). A total of 240 juveniles were observed, with an average weight of 17.91±4.87g, distributed in 20 boxes with a capacity of 500 liters each, in a completely randomized design with five treatments and four replications, containing 12 fish per replication. Five isoprotein diets (41% of crude protein) containing increasing levels of pequi oil (0.5, 1.5, 2.0, 3.8 and 5.5%) were assessed. The animals were kept in a water recirculation system, equipped with a filter, forced aeration, and a 12-hour photoperiod. To evaluate the performance, survival rate, weight gain, feed conversion, specific growth rate, protein efficiency rate, hepatosomatic index, and digestive-somatic index were analyzed. For physiological responses, hematological parameters and indexes, and differential leukocyte counts were determined. The concentration of serum protein, albumin, and globulin was also determined at the end of a 60-day period. There was no effect of the inclusion of pequi oil on weight gain, feed conversion, and protein efficiency rate (p ˃ 0.05). The specific growth rate was significantly different (p ˂ 0.05) with the reduction of treatments. An increase in the hepatosomatic index was observed in the treatments, with significant differences (p ˂ 0.05) and a linear increase, resulting in evidence of a lack of essential fatty acids. Hematocrit values showed no differences, but discrepancies were observed (p ˂ 0.05) for the number of erythrocytes, which, however, remained within the reference values for the species. The hematometric ratios also showed differences between treatments (p ˂ 0.05), remaining within the reference values, not characterizing an anemic condition in the animals. The increase in serum protein levels suggests that pequi oil starts to act as an immunostimulant. However, the use of pequi oil in juvenile tambaqui was not able to guarantee an efficient growth rate.